The rationale for the use of the combined method of immunocorrection in children with allergic bronchial asthma - E. G. Asiryan; O. V. Matyuschenko; O. N. Matsuk; N. D. Titova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
The purpose of the work is to study the clinical and immunological effectiveness of using autoserotherapy, ultrasound, as well as their combined use in children with allergic bronchial asthma.Materials and methods. During the work, 102 children aged 6 to 18 years with bronchial asthma were examined. Group A included 19 patients who received autoserotherapy. Group B patients (19 children) received ultrasound therapy in the spleen area. In group C (32 children), autoserotherapy was combined with ultrasound treatment. 32 patients with group D bronchial asthma made up the comparison group. All children included in the study received basic treatment (inhaled glucocorticosteroids).Results. Carrying out autoserotherapy in patients with bronchial asthma caused a statistically significant decrease in CD4+CD25+ T-lymphocytes (p1-3 rel.<0,05; p1-3 abs.<0,05), as well as a significant increase in CD19+CD23++ B-lymphocytes through 82-90 days from the start of the study (p2-3 abs.<0,05). After ultrasound therapy, after 12-15 days, a statistically significant decrease in the absolute level of CD4+CD25+ T-lymphocytes was observed (p1-2 abs.<0,05). The combined use of ultrasound exposure with autoserotherapy leads to an increase in the level of control of bronchial asthma, the indicators are statistically significantly higher in comparison with patients in whose treatment only basic therapy was used (pC-AСT2 <0,05; pC-AСT4<0,001; pAСT2<0,05 ; pAСT3<0,01; pAСT4<0,001). In this group of children, the level of CD4+CD25+ T-lymphocytes, CD19+CD23++ B-lymphocytes was statistically significantly reduced, was significantly lower than in the group of patients in whose treatment only basic treatment was used (pЕ2-В2 abs. CD4+CD25+<0,05; pE3-B3 abs. CD19+CD23++<0,05).